Factors Affecting Small and Medium-Sized Businesses (SMEs) Development and Growth - Harendra K.C. (Journal of Nepalese Management and Research, 2024)
Small and medium-sized enterprises (SMEs) are companies that, about more prominent firms, are smaller in income, assets, or workforce. In many countries, SMEs are often seen as critical to innovation, economic growth, and job creation. This research aimed to determine the variables impacting the growth and development of SME business in Birendranagar, Surkhet. The research focuses on five main areas: Availability of human resources, market access, government policy and provision, access to finance, and technology change. The questionnaire was designed using a theoretical framework that included the resource-based viewpoint, transaction cost economics, and institutional theory. Data were gathered from 205 SME respondents using a straightforward sample approach and a questionnaire. The study employed a quantitative exploratory research approach and was conducted using SPSS software The research found that changes greatly influenced the expansion and development of small and medium-sized businesses in market access, technology, and finance availability. On the other hand, the impact of human resources and government policy was negligible.